Pengaruh Komposisi Media Tanam terhadap Pertumbuhan dan Hasil Bawang Merah - Sugianto Sugianto; Kamelia Dwi Jayanti (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2021)
Shallot production in Central Sulawesi recorded a decline from 8.651-8.362 tons, between 2017-2018. However, the use of an accurate composition of the planting medium serves as a possible alternative to boost the yield. Also, the introduction of organic matter tends to increase the nutrient content, influence the aeration, and subsequently leads to drainage. This study is aimed at determining the effect of plant media composition on shallot growth and yield. A randomized block design comprising 4 treatments, termed soil composition, husk charcoal, and goat manure. Each treatment was repeated at 5 times to achieve 20 experimental units. The results showed that the plant media composition indicated a significant effect on the parameters of plant height at age 4 and 6 Weeks After Plantings (WAP), quantities of leaves aged 4 WAP, tillers aged 6 WAP as well as tubers per clump. Similar impacts were also reported on plant height at 2 WAP, the number of leaves aged 2 and 6 WAP, fresh tuber weight, tuber diameter, accumulated weight loss, root length, and available moisture content. Furthermore, the addition of husk charcoal and manure at a volume ratio of soil: husk charcoal: manures = 2:1:1, tends to increase the quantities of leaves, tillers, tubers per clump, as well as plant height, fresh tuber weight, and shallot bulb diameter.